'Street-level bureaucracy, management and the corrupted world of service'. Issue 5 (2nd September 2016) - Evans, Tony
Abstract : Lipsky's analysis of the implementation gap in welfare policy in 'Street-level Bureaucracy' focuses on the problem of front-line discretion but 'brackets off' the discretion of senior managers. In this paper I draw on a qualitative study to argue that senior managers can also exercise significant discretion and that their discretion can contribute to the conditions of policy confusion and contradiction, and resource inadequacy that characterise 'the corrupted world of service' of front-line discretion. In this context front-line discretion may be used by front-line staff to bridge the policy implementation gap created by senior managers.